1923
DOI: 10.1002/cber.19230560845
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische Hydrierungen unter Druck bei Gegenwart von Nickelsalzen, VI.: Nitrile

Abstract: 1988 0.1049g Sbst.: 0.1761g CO,, 0.0498g H,O, 0.117Yg BaSO,. S -M e t h y 1 a t h e r : Aus der alkalischen LSsung des Phenylguanylthiosemicarbazids mit Dimethylsulfat. WeiBe, seidige Nadeln ;tus Benzol. Stal basisch. Sintert bei etwa 1 1 5 0 unter Ubergang in €estes Phenylguanazol. C8H1,N5S. Ber. C 45.9, H 5.3, N 15.3. Gef. C 45.8, H 5.3, N 15.4. 0.1035 g Sbsl.: 0.18:M g CO,, 0.0525 g H, 0, 0.1084 g Ha SO,.Wird der Methylather in verd. Essigsgure gelost, iiberschussige I(a1iuxnferricyanid-Liisuug zuggeben und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 8 publications
2
58
0
Order By: Relevance
“…[12] 2.2 Hydrogenation of Nitriles Von Braun et al presented a scheme for the mechanism in the hydrogenation of nitriles to explain the formation of secondary amines. [23] Nitriles were hydrogenated first to the imine and then to the primary amine. The primary amine could react with the intermediate imine and form the secondary amine via a gem-diamine that could undergo either direct hydrogenolysis or elimination of NH 3 followed by hydrogenation.…”
Section: Reductive Amination Of Aldehydes and Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] 2.2 Hydrogenation of Nitriles Von Braun et al presented a scheme for the mechanism in the hydrogenation of nitriles to explain the formation of secondary amines. [23] Nitriles were hydrogenated first to the imine and then to the primary amine. The primary amine could react with the intermediate imine and form the secondary amine via a gem-diamine that could undergo either direct hydrogenolysis or elimination of NH 3 followed by hydrogenation.…”
Section: Reductive Amination Of Aldehydes and Ketonesmentioning
confidence: 99%
“…[6,23] Le Bris et al also reported that, in the reductive amination of acetone with NH 3 , isopropylamine and diisopropylamine are formed from the heterogeneous hydrogenation of the imines that are produced, respectively, from the homogeneous reaction of acetone with NH 3 and acetone with isopropylamine. It was observed that, with a Ni catalyst, isopropylamine is the main product while diisopropylamine is formed nearly exclusively when using a Pt catalyst.…”
Section: Location Of the Reaction Stepsmentioning
confidence: 99%
“…In 1923, Von Braun et al further developed the understanding of the mechanism, by proposing a route by which secondary or tertiary amines can be formed as a result of a reaction between aldimine intermediates and amine products [10]. Scheme 1 shows some of the possible side reactions that can occur when the primary amine is the target product [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation of the nitrile group is assumed as being a relatively facile transformation [15], but selectivity is of great importance in such reactions, due to the often high-purity requirements of products and multiple possibilities of side reactions [10,16]. Skeletal metal catalysts based on Ni or…”
Section: Introductionmentioning
confidence: 99%
“…4 This mechanism was originally developed to account for secondary amine formation during the hydrogenation of heptylcyanide by nickel salts. 16 When applied to NBR hydrogenation, this reaction sequence envisages crosslinks as secondary amines that are produced by an addition of fully hydrogenated nitrile to an imine intermediate. Although this mechanism can explain the efficacy of viscosity modifying additives, it has yet to be substantiated by definitive experimental results.…”
Section: Introductionmentioning
confidence: 99%